FINANCIAL STATEMENTS PRESENTATION OF NON-GOVERNMENTAL ORGANIZATION: PERSPECTIVE PSAK 45 - Siti Khajar Sudirman; Andi Nurwanah; Syamsu Alam (Universitas Islam Balitar, 2016)
This study aims to describe how the stages of preparing financial statements in non-profit organizations, referring to PSAK no. 45, to see the suitability of the statement items in each paragraph in the PSAK. The research was conducted at the PKBI NGO in South Sulawesi. The type of data used is qualitative data and the source of this research data is secondary data, namely data collected from documents and archives related to research. Data collection was carried out by observation, interviews, and documentation. While the analytical method used is descriptive analysis method, namely data analysis carried out by explaining and describing the mechanism and stages of the presentation of financial statements by the PKBI NGO South Sulawesi, referring to PSAK No. 45 on Financial Reporting of Non-Profit Organizations. The findings of this study are 1) The financial statement of non-profit organizations prepared by the PKBI South Sulawesi NGO consist of three types of reports, namely statement of financial position, activity reports, and cash flow statement in 2014 and 2015, it is in accordance with PSAK No. 45 and 2) South Sulawesi PKBI NGO has presented financial statement in accordance with PSAK No. 45. Of the twenty paragraphs regulating the financial statements of non-profit organizations, there are twelve paragraphs in accordance with the situation of the PKBI South Sulawesi NGO, namely paragraph 11, paragraph 12, paragraph 13, paragraph 14, paragraph 17, paragraph 20, paragraph 21, paragraph 22, paragraph 23, paragraph 24, paragraph 27, and paragraph 29.